As free and as just as possible : the theory of Marxian liberalism - Reiman, Jeffrey H. (Chichester ; Malden, MA : Wiley-Blackwell, 2012)
Grafting the Marxian idea that private property is coercive onto the liberal imperative of individual liberty, this new thesis from one of America's foremost intellectuals conceives a revised definition of justice that recognizes the harm inflicted by capitalism's hidden coercive structures. Maps a new frontier in moral philosophy and political theoryDistills a new concept of justice that recognizes the iniquities of capitalismSynthesis of elements of Marxism and Liberalism will interest readers in both campsDirect and jargon-free style opens.
6.2 The Limits of Property6.3 The Marxian Theory of the Conditions of Liberty; 6.4 Inside the Marxian-Liberal Original Position; 6.5 The Difference Principle as a Historical Principle of Justice; 7: As Free and as Just as Possible: Capitalism for Marxists, Communism for Liberals; 7.1 The Just State; 7.2 Capitalism for Marxists; 7.3 The Marxian-Liberal Ideal: Property-Owning Democracy; 7.4 Communism for Liberals; Conclusion: Marx's "Liberalism," Rawls's "Labor Theory of Justice"; Index.
Includes bibliographical references and index.
Print version record.
Keywords: Rawls, John, -- 1921-2002.; Rawls, John, -- 1921-2002.; Rawls, John, -- 1921-2002.; Liberalism -- Philosophy; Philosophy, Marxist; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism; Liberalism -- Philosophy; Philosophy, Marxist; Electronic books